Creativity as Cognitive Ability and Thinking Process: A Narrative Review of Two Interrelated Perspectives - Hayatun Nufus; Dhoriva Urwatul Wutsqa; Ariyadi Wijaya; Riyan Hidayat (FKIP Universitas Lampung, 2026)
The development of 21st-century education demands strengthening mathematical creative thinking as part of higher-order thinking. However, the literature shows a conceptual fragmentation that positions mathematical creativity as both a cognitive process and a measurable ability. This study aims to synthesize and integrate these two perspectives through a systematic literature review (SLR) guided by the PRISMA 2020 guidelines, resulting in a more comprehensive conceptual framework. The review process was carried out through the stages of identification, screening, eligibility, and inclusion of literature from the Scopus database with strict selection criteria. Of 124,278 initial documents, 34 scientific articles were identified that met the criteria for the main unit of analysis. The analysis was conducted through a cross-study conceptual synthesis to identify the characteristics of creativity as a process and an ability, and to examine the relationship between the two. The results of the study indicate that the process approach emphasizes the dynamics of the stages of creative thinking (e.g., preparation, incubation, illumination, and verification). In contrast, the ability approach emphasizes measurable indicators such as fluency, flexibility, originality, and elaboration. The main finding of this study is the development of an integrative conceptual framework of process–ability, which positions mathematical creativity as a multidimensional construct that simultaneously connects cognitive dynamics with measurable performance. The contribution of this study is not only a critical synthesis but also an attempt to offer a new conceptual flowchart that integrates creative thinking as a process and as an ability, and is expected to serve as the basis for developing more holistic learning and assessment designs. The implications of this study indicate the importance of developing assessment instruments that can capture both process and product simultaneously. Thus, this study expands theoretical understanding while providing new methodological directions in mathematics education research and practice. Keywords: creative thinking process, creative thinking ability, mathematics, mathematics education.